PENGARUH STRATEGI PEMBELAJARAN TERHADAP KEMAMPUAN BERFIKIR KREATIF SISWA PADA MATERI AKIDAH AKHLAK DI MI MIFTAHUL HUDA KEBOLEDAN KELAS 5 - Ely Maghfiroh; Taukhid Mubarok (CV. ADIBA AISHA AMIRA, 2025)
Learning is an activity that involves many different elements such as: students, teachers, curriculum, facilities and infrastructure. Before starting learning, teachers should pay attention to various elements of the learning system, such as: This includes learning preparation, planning, preparing relevant material, developing methods that are adapted to students' situations and conditions, as well as providing learning resources and other media. Learning tools play an important role in the success of the learning process, so learning tools must be created and followed by teachers. Data was obtained through instruments in the form of observation sheets, interview guides and questionnaires, followed by descriptive analysis. Based on the results of the validator evaluation, the learning device is declared valid. Proven to increase learning activities and improve students' creative thinking abilities. The learning tools developed in this research can be used by Aqidah Akhlak teachers and become motivation to always develop professional competence, especially in the learning process. The thinking skills that need to be developed by students are divided into two types, namely higher order thinking skills and lower order thinking skills. High-level thinking skills in the cognitive realm include students' abilities to analyze, evaluate, and create, all of which are advanced stages of low-level thinking skills which consist of students' skills in remembering, understanding, and applying. A directed process of critical thinking for mental activities using reason in solving problems, analyzing opinions carried out scientifically. Critical thinking is the ability to express opinions in a systematic way that enables students to form their own opinions with a deep understanding of an issue.